This too shall pass! - Latorre Ariño, Marino (2020)
The article describes the appearance of COVID-19 in an unpredictable way on planet Earth and the consequences it has had for humanity, which was not prepared for a pandemic of this magnitude. It relates the psychological and material situation in which many children and young people --generation X, Y, Z -- lived before the pandemic and the consequences they have had to live in this experience of lockdown due to the quarantine imposed and what lessons can be drawn from the situation experienced. It also deals with the origin and form of spread of COVID-19, the possible political and economic interests that may have given rise to it, as well as the health policies implemented by different countries, and asks whether science is the solution. It concludes with a reflection on whether this threat can be reversed into an opportunity for humans to reflect and, after living this experience, learn to live in a more humane way and whether a new and better world order can be created for all.